Naringin attenuates cerebral ischemia-reperfusion injury in rats by inhibiting endoplasmic reticulum stress - Wang Li (De Gruyter, 2021)
This investigation was carried out with an aim of exploring neuroprotection by naringin (Nar) in rats with cerebral ischemia-reperfusion (CI/R) injury and its mechanism.